Strategi Komunikasi Pemasaran Produk Smartphone Pada Perusahaan BRP Cellular Group Tulungagung - Diki Setiawan; Mutrofin (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2022)
Integrated Marketing Communication is still very widely used in the business world. The theory is the basis for the running of the activities of a marketing communication activity in a company. This article aims to find out about the Integrated Marketing Communication of the Tulungagung BRP Cellular group company. Integrated Marketing Communication consists of five models, namely 1. Advertising, 2. Sales Promotion. 3. Public Relations, 4. Personal Selling, and 5 Direct Selling. The research paradigm used is a qualitative paradigm with observation and interview research methods. The result of this research is that BRP has implemented 5 models of Integrated Marketing Communication in various ways, such as using news media, online, sepaduk, baleho and events, then also short-term promotion by going directly to the public to offer products, and don't forget to use public relations to continue to form a positive image carried out by all BRP Celluler crew, and using social media such as Instagram, facebook, and tiktok to better reach the online market.